PENGEMBANGAN KEMAMPUAN MERANCANG DAN MELAKSANAKAN KEGIATAN LABORATORIUM FISIKA BERBASIS INKUIRI BAGI MAHASISWA CALON GURU - Wiyanto, - (2005)
This study aimed to develop the prospective physics teacher's capabilities in designing and implementing an inquiry-based laboratory activity. The study was conducted by using a research and development design. The subject of this study was the third year of the prospective physics teachers of an institution for pre-service teacher education. There were seven aspects that supposed to be able to support development of the prospective teacher's capabilities in designing and implementing an inquiry-based physics laboratory activity, i.e. (1) determining the purpose of the laboratory activity design; (2) determining the appropriate experiment; (3) determining the appropriate laboratory materials; (4) determining the set up and diagram of the experiment; (5) planning and implementing the procedure of the experiment; (6) constructing the inquiry-based student worksheets; and (7) constructing assessment of students achievement of a physics laboratory activity. These aspects were developed in a course, namely the Laboratory for Physics Education, which was carried out through three steps, i.e. modeling, designing, and implementing. Achievement of these aspects was evaluated by pre- and post- of both paper-and-pencil and performance test, observation, worksheets and the laboratory activity designs produced during the course. The result showed significant gains in all of the aspects. The success of the study was also justified by positive responses of the prospective teachers during the course. It is suggested to optimize the study by developing these aspects in other appropriate courses supported by sufficient laboratory services.